Theory of Matrices - Perlis, Sam (Cambridge, Massachusetts: Addison-Wesley Press, 1952)
The main theme of this book is the establishment of the well-known canonical forms. Rank, non-singularity, and inverses are introduced in connection with the development of canonical matrices under the relation of equivalence, and without the intervention of determinants. Congruence and Hermitian congruence are the next major topics. There is generous supply of exercises including adequate amounts of numerical work, but bearing heavily on simple theoretical questions.
ne 7/03/2018
Loan
Keywords: Matrices